Kekosongan Norma terhadap Pilihan Childfree dalam Hukum Perkawinan Indonesia: Perspektif Hak Asasi Manusia - AHMAD MUBARAK; Nurul Azkia; Iqnaul Umam Ashidiqi; Muhamad Rahmani Abduh; Novy Listiana (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The childfree phenomenon reflects a paradigm shift in interpreting the purpose of marriage in Indonesia, from a reproduction-oriented framework towards the fulfilment of individual rights. This study employs a normative juridical method, utilising statutory, conceptual, and comparative approaches. The findings indicate a normative gap within positive law concerning the choice to remain childfree, as well as a conflict between marriage law, which is institutionally oriented, and human rights law, which emphasises individual freedom. It is concluded that childfree exists within a legal grey area, thereby necessitating normative harmonisation to ensure legal certainty and the protection of reproductive rights.